Peer pressure and self-statement mechanism to mitigate management behavior in budgetary slack: An experimental approach - Apriwandi Apriwandi; Debbie Christine (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2023)
This study evaluates the susceptibility of management (especially management accountants) in creating budgetary slack by violating company policies. Reducing the creation of budgetary slack was evaluated by the relationship of the effects of peer pressure and perceived self-statement mechanisms within the scope of each social ethical dimension. Experimental results with 133 management accountants show that social and ethical friction can reduce the creation of budgetary slack by emphasizing peer pressure and self-assessment mechanisms. All experimental subjects could not violate company policy and it was proven by decreasing budgetary slack when faced with conditions without peer pressure and without a self-assessment mechanism. This finding provides evidence that budgetary slack is created when management is fully involved in setting the company's budget without any control from colleagues or leaders. The importance of social ethics in budgeting is raised by collegiate decisions in the team and creates a self-assessment mechanism for managers. Thus, resistance to creating budgetary slack can be increased and managers are held accountable for making budgetary decisions.